Liderazgo directivo, modelo de medida del constructo para aplicación en educación básica regular (Investigaciones) - Rossi Valverde, Ricardo Manuel (2021)
In this quantitative research work the Confirmatory Factor Analysis was used with the following objective: To adjust a measurement model of the directive leadership construct for its application in Regular Basic Education. The sample consisted of 206 teachers from La Libertad, in Peru. The rotated component matrix and the composite reliability, extracted variance and goodness of fit indices (X2normed = 2,90; NFI = 0,93; IFI = 0,95; TLI = 0,94; CFI = 0,95 and RMSEA = 0,096) confirmed that the studied construct is solid with 4 dimensions and 13 items. The adjusted measurement model will allow to assess the levels of leadership in the directors of the educational institutions of Regular Basic Education, acceptably.